Dynamics of changes in indicators of oxidative stress in the early and late terms of correction of experimental opioid exposure - Paltov , Ye.V. (Морфологія / Morphologia / Morfologìâ, 2025)
The purpose of the study is to investigate changes of oxidative stress indicators during subchronic and chronic periods of opioid exposure when corrected with pentoxifylline. In order to achieve the set goal, we have studied the sources of scientific medical domestic and world literature. The results. As a result of the correction carried out by us during weeks 3,4,5 and 6 of opioid exposure, the value of the blood malonaldehyde index at week 6 was the maximum in the “nalbuphine + pentoxifylline” subgroup and was 6,39±0,41, which was 35,33% greater value of the control group, thus approaching the relative difference to the group of animals that were administered nalbuphine for 10 weeks. In the withdrawal subgroup, the indicator had no significant difference compared to the 6-week group, and in the “withdrawal + pentoxifylline” subgroup – it had positive dynamics only in comparison with the “nalbuphine + pentoxifylline” subgroup. The value of the index of diene conjugates of the “withdrawal + pentoxifylline” subgroup had lager fluctuations compared to malondialdehyde – the average value was 41,52±1,36, which was actually on the same level as the value of control group – 41,06±1,63. In the “cancellation” subgroup, the index of diene conjugates did not have a significant difference compared to the 6-week group, and in the “nalbuphine = pentoxifylline” subgroup it was greater than the value of this indicator in the 6-week group and was 46,46±1,59 (control 40,47±2,57, p<0,005). At the same time, in the “withdrawal + pentoxifylline” subgroup, the value of ceruloplasmin increased to the 287,50±8,05, which was close to that in the group of control animals – 294,28±9,13 (p=0,61) and was not statistically significant difference when compared. As a result of the correction carried out by us in the interval of 7, 8 ,9 and 10 weeks of opioid exposure, the value of the blood malondialdehyde index at week 10 in all subgroups of the correction was less than that in the group at week 10, which was 6,24±0,45. Malonaldehyde values were the lowest in the “withdrawal + pentoxifylline” subgroup compared to the 10 -week group. However, despite the fact that this indicator had positive dynamics in comparison with the 10-week group and other correction subgroups, it remained significantly higher than the indicator of the control group, which was 4,88±0,19 (p<0,05), this difference was 13,74%. In the “cancelation” subgroup, the index of diene conjugates did not have a significant difference compared to the 10-week group, and in the “nalbuphine + pentoxifylline” subgroup it was greater than the value of this indicator in the 10-week group and was 46,80±1,12, which was 4,41% more than the indicator of the 10th week group and 12,49% more than the indicator of the control group (control 41,60±3,02, p<0,05). The dynamics of changes in ceruloplasmin in subgroups of week 10 correction was similar to that of diene conjugates. Thus, in the “withdrawal + pentoxifylline” subgroup, the value of ceruloplasmin increased to 278,60±4,30, however, despite such positive dynamics, this indicator remined 4,43% lower than that in the control group – 291,51±5,85, and this difference remained statistically significant (p<0,05). Conclusion. The greatest positive dynamics in the subgroups of week 6 correction was observed in the “withdrawal + pentoxifylline” subgroup, while the dynamics of diene conjugates and ceruloplasmin indicators were equal to those in the control group. The greatest positive dynamics in the 10-week correction subgroups was observed in the “withdrawal + pentoxifylline” subgroups, however, despite the positive dynamics, especially in the indicators of diene conjugates and ceruloplasmin, it was not possible to reach the level of such indicators in the control group.